Deteksi, Monitoring Dan Pencegahan Insider Threat : As A Survey - Muhamad Firmansyah; Yurry Matufira; Beny Nugraha - Universitas Mercu Buana (Indonesian Journal of Networking and Security (IJNS), 2016)
Abstract - many organizations using networks such as the Internet in data management. With a network of course the threat continues to threaten the confidentiality, integrity and availability of the system. Many organizations do this prevention, but they usually focus on the threat from the outside. The threat from within is more easily abuse the access authority often escape the focus of prevention. Has been a lot of research that explores the problems of insider threat. The approach taken out of the habit theory proposed by Moyano, Bayesian Network models and preliminary model of the End User Computing (EUC). This paper defines the threat from within (Insider Threat) with techniques of detection and prevention, and then do the mapping for the management of the system against the insider threat. Keywords: insider threats, detection, monitoring, sociology, management system Abstrak – Organisasi banyak menggunakan jaringan seperti internet dalam pengelolaan data. Dengan jaringan tentu saja ancaman senantiasa mengancam confidentiality, integrity dan availability system. Banyak organisasi melakukan pencegahan ini, namun biasanya fokus mereka pada ancaman dari luar. Adapun ancaman dari dalam yang lebih mudah menyalahgunakan otoritas akses sering luput dari fokus pencegahannya. Telah banyak penelitian yang mengetengahkan permasalahan insider threat. Pendekatan diambil dari teori kebiasaan yang diajukan oleh Moyano, model Bayesian Network dan model preliminary pada End User Computing (EUC). Tulisan ini mendefinisikan ancaman dari dalam (Insider threat) dengan teknik-teknik pendeteksian dan pencegahannya dan kemudian melakukan pemetaan untuk pengelolaan manajemen sistem terhadap insider threat. Kata kunci: insider threat, detection, monitoring, sociology, system management